Applying a rural development lens to migration policy in Kyrgyzstan - Murzakulova, A. (University of London, 2022)
Development trends in Kyrgyzstan include declining agricultural production, a steady increase in remittances to rural areas from labor migration and an increasing role for the non-agricultural sector in the rural economy. These trends suggest that labor migration is having a transformative effect, with significant opportunities for rural development, but also challenges ahead. Even though migration has a huge impact on the country’s economy (remittances account for some 30% of the country’s GDP), to date migration governance focuses mainly on the rights protection of migrants and does nothing about sending communities and rural development policy. The attractiveness of rural villages for return migration and the well-being of those left-behind should be a major focus for migration policy along with the inclusion of migration as cross-cutting issue in rural development policy at all levels.